IMF prescriptions for Latin America in the 1980s and East Asia in the 1990s : a comparative analysis. - Chong, Kam Tuck. (2008)
This dissertation examines the role of the IMF and their policy prescriptions for Latin American crisis in the 1980s and the East Asian crisis in the 1990s. A comparative analysis approach is used to draw out similarities and differences in approaches adopted by the IMF to both crisis situations.